Ablation of Arginase II Spares Arginine and Abolishes the Arginine Requirement for Growth in Male Mice. Issue 8 (5th July 2017) - Didelija, Inka C; Mohammad, Mahmoud A; Marini, Juan C
Abstract: Background: Arginine is considered a semiessential amino acid in many species, including humans, because under certain conditions its demand exceeds endogenous production. Arginine availability, however, is determined not only by its production but also by its disposal. Manipulation of disposal pathways has the potential to increase availability and thus abolish the requirement for arginine. Objective: The objective of the study was to test the hypothesis that arginase II ablation increases arginine availability for growth. Methods: In a completely randomized design with a factorial arrangement of treatments, postweaning growth was determined for 3 wk in male and female wild-type (WT) mice and arginase II knockout mice (ARGII) on a C57BL/6J background fed arginine-sufficient [Arg(+); 8 g arginine/kg] or arginine-free [Arg(−)] diets. Tracers were used to determine citrulline and arginine kinetics. Results: A sex dimorphism in arginine metabolism was detected; female mice had a greater citrulline flux (∼30%, P < 0.001), which translated to greater de novo synthesis of arginine (∼31%, P < 0.001). Female mice also had greater arginine fluxes ( P < 0.015) and plasma arginine concentrations ( P < 0.01), but a reduced arginine clearance rate ( P < 0.001). Ablation of arginase II increased plasma arginine concentrations in both sexes (∼27%, P < 0.01) but increased arginine flux only in males ( P < 0.01). The absence of arginine in the diet limited the growth of male WT mice ( P < 0.01), but had no effect on male ARGII mice ( P = 0.12). In contrast, WT females on the Arg(−) diet grew at the same rate and achieved final weight similar to that of female WT mice fed the Arg(+) diet ( P = 0.47). Conclusion: The ablation of arginase II in male mice spares arginine that can then be used for growth and to meet other metabolic functions, thus abolishing arginine requirements.